2016
DOI: 10.1061/(asce)ae.1943-5568.0000171
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Partitions and Floor Vibration Serviceability

Abstract: The results presented in this study will be of interest to design engineers and researchers in the area of vibration serviceability of floor systems, as it highlights the potential of non-structural elements to reduce the floor vibration response to acceptable levels to transmit vibrations between floors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…It has been illustrated that non-structural elements can have significant effects on the dynamic responses of the floor systems of buildings; evidence for such effects was observed in determining the dynamic parameters of both slender floor systems [ 26 , 27 ] and traditional concrete floor systems, as detailed [ 28 ].…”
Section: Serviceability Testmentioning
confidence: 99%
“…It has been illustrated that non-structural elements can have significant effects on the dynamic responses of the floor systems of buildings; evidence for such effects was observed in determining the dynamic parameters of both slender floor systems [ 26 , 27 ] and traditional concrete floor systems, as detailed [ 28 ].…”
Section: Serviceability Testmentioning
confidence: 99%
“…Of these areas, the vibration response may have a predetermined limit in order to be assessed and if that limit exceeded what would be the probability of occurrence. Devin et al [118] also ascertained this method under a single person loading to produce a "contour plot of responses". In addition, there are a number of commercial software packages, such as Oasys GSA [119], Autodesk Robot Structural Analysis [120], SAP2000 [121] and ETABS [122], that define harmonic footfall analysis for a single person excitation at stationary positions based on design guidelines, such as Concrete Centre [27], SCI P354 [18] and AISC DG11 [17].…”
Section: Probabilistic Response Distributionmentioning
confidence: 99%
“…Regarding full-height non-structural partitions, Middleton and Pavic performed a modal test on a structure in various stages of construction and proved that the partitions can increase the overall frequency and local stiffness of the structure, with the damping of structure increasing as well [32]. Devin et al investigated the potential beneficial effects of nonstructural partitions on the vibration serviceability of a floor due to walking excitation through a finite-element model and found that the addition of nonstructural partitions successfully reduced floor acceleration and helped the floor to satisfy the vibration serviceability criterion for office floors [33]. Andersen et al focused on wooden floors built as an assembly of particleboard and timber joists with a finite element method and concluded that non-structural mass must be taken into account in a dynamic assessment of a wooden floor, which also has a significant effect on its modal properties [34].…”
Section: Introductionmentioning
confidence: 99%